Clinical Practice Guideline by the Pediatric Infectious Diseases Society and the Infectious Diseases Society of America: 2021 Guideline on Diagnosis and Management of Acute Hematogenous Osteomyelitis in Pediatrics. (5th August 2021) - Woods, Charles R; Bradley, John S; Chatterjee, Archana; Copley, Lawson A; Robinson, Joan; Kronman, Matthew P; Arrieta, Antonio; Fowler, Sandra L; Harrison, Christopher; Carrillo-Marquez, Maria A; Arnold, Sandra R; Eppes, Stephen C; et al.
Abstract: This clinical practice guideline for the diagnosis and treatment of acute hematogenous osteomyelitis (AHO) in children was developed by a multidisciplinary panel representing Pediatric Infectious Diseases Society (PIDS) and the Infectious Diseases Society of America (IDSA). This guideline is intended for use by healthcare professionals who care for children with AHO, including specialists in pediatric infectious diseases, orthopedics, emergency care physicians, hospitalists, and any clinicians and healthcare providers caring for these patients. The panel's recommendations for the diagnosis and treatment of AHO are based upon evidence derived from topic-specific systematic literature reviews. Summarized below are the recommendations for the diagnosis and treatment of AHO in children. The panel followed a systematic process used in the development of other IDSA and PIDS clinical practice guidelines, which included a standardized methodology for rating the certainty of the evidence and strength of recommendation using the GRADE (Grading of Recommendations Assessment, Development and Evaluation) approach. A detailed description of background, methods, evidence summary and rationale that support each recommendation, and knowledge gaps can be found online in the full text.